Kompetensi Managerial Kepala Sekolah dalam Upaya Peningkatan Kualitas Pendidikan di SDI Ulumiyah Al-makruf - hasan sadili; Mustajib (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
The headmaster is a skipper in an educational institution, whether or not a leader will determine the quality of the institution, a person who becomes the principal must have certain criteria that can bring the institution to achieve the objectives of the vision, mission including planning, developing the organization, empowering resources and carrying out supervision of programs and performance. We researchers are interested in researching the managerial competence of a principal at SDI Ulumiyah Al Makruf in improving the quality of education in his institution. Therefore, in this article we will discuss several things related to competence, including about 1. Principal competence, 2. Managerial ability of the principal, and 3. Quality of education